Koncepcja nadzoru wiodącego (Lead Supervisior) nad rynkiem finansowym UE - Kurek, Robert (The Concept of Lead Supervisor Over the European Union Financial Market, 2008)
The article presents one of supervision integration concepts over the EU financial market, the so--called Lead Supervisor. The concept was developed by the European Financial Services Round Table (EFR). The EFR is a market institution gathering representatives of the supply sector of the European financial market which aims at promoting the homogenous market of financial services, including the support for effective and efficient supervision within the whole EU. The Lead Supervisor is supposed to present the supervision covering both different parts of financial sector and, at the same time, different EU countries. In the EFR concept such organization of supervisory structures would facilitate the creation of conditions for equal competition among all financial companies and become helpful in the situation of crisis management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 181-188